Awareness of alcohol advertisements and perceived influence on alcohol consumption: a qualitative study of Nigerian university students. (2nd January 2017) - Dumbili, Emeka W.; Williams, Clare
Abstract: Despite the growing alcohol marketing activities of the transnational alcohol industries in Nigeria, little research has focussed on their effects on Nigerian youths. This study explores students' awareness of electronic and outdoor alcohol advertisement on campus and around students' off-campus residential and leisure sites, and the extent to which they perceive it to affect their drinking. Thirty-one in-depth interviews were conducted with male and female undergraduate students (aged 19-23 years) from a south-eastern Nigerian university. Alcohol advertisements on television, posters, billboards and the branded fences of bars are common on campus and around students' off-campus residential and leisure spaces. While students were exposed to television alcohol advertisements aired during football games, movies and news hours, they regularly saw point-of-sale and other outdoor advertisements on and around the campus. Students demonstrated sophisticated levels of awareness of alcohol advertisements, to the extent that they 'identified' brand names, vividly described the advertising messages they had seen and named specific bars, restaurants and other sites where they had seen alcohol advertisements regularly. While alcohol advertisement influenced men to consume new products, it also affected their brand preference on a permanent basis. Although alcohol advertisements appear not to have influenced the women, it is argued that this was because they were exposed to the advertisements of alcoholic brands that are categorised as 'men's alcohol' in Nigeria. The results suggest that while effective monitoring of electronic and outdoor advertisements should be reinforced, policymakers may consider replacing self-regulation with evidence-based alcohol control regulatory measures in Nigeria.